GAGASAN PENINGKATKAN KUALITAS PENDIDIKAN DI ERA SEKARANG DALAM PERSPEKTIF JACOB BRONOWSKI - Dadi, Kanisius Komsiah; Djatmiko, Wisnu; Muslim, Suyitno (Lembaga Penelitian STKIP Widya Yuwana, 2025)
This article explores the idea of improving the quality of education in the modern era by referring to Jacob Bronowski's thoughts in chapter II: The Harvest of the Seasons contained in the book The Ascent of Man. From the study of this chapter, the researcher found an interesting idea that deserves to be studied more deeply, namely about human development through discovery, creativity, and intellectual ability in The Harvest of The Seasons. This study provides a relevant perspective in the current educational context. As a conclusion from the results of the literature study supported by field studies, Bronowski's approach to human intellectual development at that time can be applied in the modern education system to face the challenges of the digital era and globalization. This study highlights three main perspective of Bronowski, namely: (1) Individual skills of learners grow and develop through an effective and efficient learning process; (2) Improving the learning process and adapting technology that continues to develop; and (3) The quality of education that can improve social welfare. These three points of thought can be used as the basis for the modern pedagogy paradigm, namely for the renewal of the curriculum and teaching methods that are more adaptive and relevant to the needs of the times. The results of this research are expected to contribute to developing an educational model that can improve the intellectual quality of students and prepare them to play an active role in the knowledge society.